Legalitas Pelantikan Kepala Pemerintah Negeri Berdasarkan Peraturan Daerah Kota Ambon Nomor 10 Tahun 2017 Tentang Pengangkatan, Pemilihan, Pelantikan dan Pemberhentian Kepala Pemerintah Negeri - Jeanerry Muriany, Bringelia; Salmon, Hendrik; Mustamu, Julista (LPPM Universitas Ekasakti Padang, 2024)
A traditional country of course has a Head of State Government or more often called a King, a King is a child of a Traditional State who is appointed or elected from the Mata Rumah Parentah to lead the State, Ambon City Regional Regulation Number 10 of 2017 concerning Appointment, Election, Inauguration and dismissal of the Head of State Government is the basis of the rules that serve as a reference in the implementation of obtaining a Head of State Government, but often in carrying out customary mechanisms, both appointment, election and inauguration, it is not in accordance with regional regulations, which of course gives rise to legal consequences. Purposes of the Research : This research aims to determine and analyze the legality of the inauguration of the Head of the State Government based on Ambon City Regional Regulation Number 10 of 2017 concerning the Appointment, Election, Inauguration and Dismissal of the Head of the State Government Methods of the Research : This writing uses normative research methods, with the problem approach used being the statutory approach, conceptual approach, historical approach and case approach. The sources of legal materials in this writing are primary, secondary and tertiary legal materials. The technique for collecting legal materials uses library research which is then analyzed qualitatively to answer the problems being studied. Results/Findings/Novelty of the Research : The results of this research show that the legality of an inauguration of a head of state government must be based on applicable regional regulations, Ambon City Regional Regulation Number 10 of 2017 concerning the appointment, election, inauguration and dismissal of heads of state government, but the legality of the inauguration of heads of state government is not only about the inauguration mechanism. appropriate but also from previous procedures, both appointment and election, if the appointment or election process is carried out incorrectly, it will of course have an impact on the process of inaugurating the head of the state government so that it will give rise to legal consequences that must be accepted, namely the cancellation of the inauguration of the head of the state government, the appointment of temporary officials, demands law, administrative sanctions, government instability and even community losses